Analisis Kinerja Keuangan dengan Metode Almant Z- Score pada PT.Terregra Asia Energy,Tbk - Ashari, Nala Oktaviani; Oktariani, Refi; Banjarnahor, Denisa Natalia (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to analyze the financial performance and predict the potential for bankruptcy at PT Terrega Asia Energy, Tbk using the Altman Z-Score model. This study uses a descriptive approach by utilizing secondary data in the form of PT Terrega Asia Energy, Tbk's financial statements for the 2020-2022 period, which can be accessed through the Indonesia Stock Exchange (IDX) website at https://www.idx.co.id/ and other official sources. The analysis is carried out by calculating and interpreting financial ratios including liquidity, profitability, leverage, and activity. The Z-Score model is used as a predictive tool for potential bankruptcy based on certain financial ratios. This analysis is expected to serve as a reference for management in identifying financial risks and formulating improvement strategies. Furthermore, the Z-Score is calculated based on the Altman formula to determine the company's financial health. The results of the analysis show that PT Terrega Asia Energy Tbk is in the